2011
DOI: 10.2105/ajph.2011.300165
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Well-Being in Washington State Military Families

Abstract: Parental military deployment is associated with increased odds of impaired well-being among adolescents, especially adolescent boys. Military, school-based, and public health professionals have a unique opportunity to develop school- and community-based interventions to improve the well-being of adolescents in military families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
102
5
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(117 citation statements)
references
References 45 publications
6
102
5
4
Order By: Relevance
“…Military youth in school on a Naval Air Station-Joint Reserve Base reported more conduct problems than population norms, but there were no differences between youth who did and did not have a parent deploy in the last year (Morris and Age 2009). In another sample of military youth in grades 8, 10, and 12, however, a history of parent deployment was associated with the following: depressed mood, suicidal ideation and binge drinking among 8th grade girls and boys; low quality of life among 8th grade boys; depressed mood among 10th and 12th grade girls and boys; and low quality of life and suicidal ideation among 10th and 12th grade boys (Reed et al 2011). Similarly, among students in the 5th, 7th, 9th, and 11th grades in military-connected schools in Southern California, youth substance use was associated with the number of parental deployments (Gilreath et al 2013).…”
Section: Current Eramentioning
confidence: 90%
“…Military youth in school on a Naval Air Station-Joint Reserve Base reported more conduct problems than population norms, but there were no differences between youth who did and did not have a parent deploy in the last year (Morris and Age 2009). In another sample of military youth in grades 8, 10, and 12, however, a history of parent deployment was associated with the following: depressed mood, suicidal ideation and binge drinking among 8th grade girls and boys; low quality of life among 8th grade boys; depressed mood among 10th and 12th grade girls and boys; and low quality of life and suicidal ideation among 10th and 12th grade boys (Reed et al 2011). Similarly, among students in the 5th, 7th, 9th, and 11th grades in military-connected schools in Southern California, youth substance use was associated with the number of parental deployments (Gilreath et al 2013).…”
Section: Current Eramentioning
confidence: 90%
“…Participants in this study had more emotional difficulties than did national samples. Reed et al (2011) found significant associations between parents' military service and several measures of well-being, including incidence of depressed mood and suicidal ideation; results differed somewhat based upon gender. Both these studies' results are in keeping with those of previous qualitative work, which demonstrated that parental combat deployment negatively affects adolescents' emotional and psychological health.…”
Section: Adverse Outcomes For Children Of Military Familiesmentioning
confidence: 88%
“…The return of a parent from an extended absence is most often met with joy and relief; still, these might also be accompanied by the stress, confusion, and distress resulting from the painful events the formerly deployed parent has experienced. Post-deployment, children are challenged by having to rebuild emotional connection with the service member while renegotiating roles and duties (Reed et al 2011;Riviere and Merrill 2011). These challenges increase exponentially when the returning soldier has experienced physical or psychological injury.…”
Section: Military Children In a Changing Family Systemmentioning
confidence: 99%
“…The impact of military stressors on health outcomes among MDY is unclear. Some studies indicate that parental deployment to a war zone and relocations have a negative impact (Barnes, Davis, & Treiber, 2007;Bradshaw, Sudhinaraset, Mmari, & Blum, 2010;Chandra et al, 2010;Gilreath et al, 2013;Gorman, Eide, & Hisle-Gorman, 2010;Huebner, Mancini, Wilcox, Grass, & Grass, 2007;Lester et al, 2010;Reed, Bell, & Edwards, 2011), whereas other studies of this population have not found a negative impact (Kelley et al, 2001;Strobino & Salvaterra, 2000;Weber & Weber, 2005). However, to our knowledge, no study has examined the relationship between these military stressors and sexual behaviors among MDY.…”
Section: Introductionmentioning
confidence: 94%